IDENTIFIKASI ANTALGIN DALAM JAMU PEGAL LINU SECARA KROMATOGRAFI LAPIS TIPIS - Supartiningsih Supartiningsih; Eka Margaret Sinaga; Maringan Silitonga; Hotvera Marianis (Jurnal Farmanesia, 2019)
Traditional medicine is an ingredient or ingredient in the form of plant material, animal material, mineral material, preparation of extracts (galenic), or a mixture of these materials which have been used for generations. Jamu is traditional medicine, in general, herbal medicine cannot cure all kinds of diseases and its natural effect is not as fast as chemical drugs. Lately, medicinal chemicals are often added which are prohibited under the provisions of BPOM (Food and Drug Supervisory Agency). Antalgin is an analgesic-antipyretic and anti-inflammatory drug. Identification of antalgin in herbal aches and pains by thin layer chromatography aims to determine whether the herbal aches and pains circulating around Jalan Captain Muslim, Medan city contain levorphanoll drug chemicals or not. Antalgin identification in herbal pain relief was applied using Thin Layer Chromatography method with 60 F Silica gel stationary phase and chloroform-acetone-toluene (65: 25:10) mobile phase. From the results of identification by thin-layer chromatography (TLC) on herbal pain relief, it was found that the Rf value of the chromatogram spot on the levorphanol 0.16 reference standard was close to the sample Rf value (E) of 0.12. Based on the examination that has been carried out, it can be concluded that the positive herbal pain relief contains levorphanol drug chemicals so that the sample (E) tested does not meet the requirements.